DETERMINAN PENDAPATAN PEDAGANG PEREMPUAN DI PASAR BADUNG - Anak Agung Istri Ngurah Marhaeni; Hotmarina Hutahaean (E-Jurnal Ekonomi Pembangunan, 2025)
The main problem faced by humans in living life is the existence of various kinds of life needs. Therefore, to meet the needs of human life, income is needed. Nowadays, the father's living needs are met as the head of the household who works, but in some situations many families whose needs are not met if they only rely on the father's income. This is what makes women enter the world of work, either working independently or working with other people. This research aims to analyze the simultaneous and partial influence of capital, location, variations in types of merchandise, and people's purchasing power on the income of women traders in the Badung market and analyze the role of people's purchasing power in moderating the influence of types of merchandise on income. This research uses quantitative methods. The sample for this research consisted of 92 female trader respondents in the Badung market. The analytical method used in this research is descriptive analysis and moderated regression analysis. The research results show that capital, location, variations in types of merchandise and people's purchasing power simultaneously influence the income of women traders in the Badung market. Capital and type of merchandise partially have a positive and significant effect on the income of female traders at Badung Market. Location and people's purchasing power partially have a negative and significant effect on the income of women traders at Badung Market. And people's purchasing power is a moderating variable that strengthens the influence of the type of merchandise on the income of women traders in the Badung Keyword : lorem, ipsum, dolor